The Accessibility and Acceptability of Health Services in Remote Rural Areas - Mutiara Ramadhani; Sukri Palutturi; Amran Razak; Muhammad Yusran Amir; M. Tahir Abdullah (Asia Pacific Journal of Health Management)
Health services depend on community facilities and infrastructure, particularly in rural areas. If facilities and infrastructure are not improved, it is feared that equitable distribution, including accessibility and acceptability of health services, will be difficult. This challenge still exists in underdeveloped villages. The purpose of this study was to analyze the effect of accessibility and acceptability factors on the level of patient satisfaction in underdeveloped villages. A quantitative research type, analytical survey with cross-sectional approach was conducted. Sampling, using the Slovin formula, resulted in 287 respondents. Data were collected using a questionnaire. There was a significant relationship between accessibility (p=0.001) and acceptability (p=0.002) on the level of patient satisfaction in underdeveloped villages. However, accessibility was the most significant factor influencing patient satisfaction at the multivariate level (Exp(B)=3.639 95% CI=1.547-6.137, p=0.019). Health facilities in rural areas still need to be improved, especially in terms of accessibility, to attract the attention of the community to seek care.